Effectiveness of Curcuma Longa and Piper betel leaf Extracts on Vaginal Discharge: A Pre-Experimental Study - Yunita, Emi; Parwati, Ni Wayan Manik (Jurnal Kebidanan Midwiferia, 2026)
Vaginal discharge is basically a reproductive complaint that is always experienced by women. Herbal treatments such as Curcuma longa and betel leaves have antimicrobial and anti-inflammatory properties. This study aims to determine the effectiveness of Curcuma longa and piper piper betel leafextracts in preventing and treating vaginal discharge in women of reproductive age. This study used a pre-experimental design with a pretest-posttest group conducted on 35 women of childbearing age (WUS) aged 20-45 years who were determined using purposive sampling. Respondents were given 200 mL of extract orally consumed three times a week for one month. Classification of vaginal discharge severity was categorized as: mild, moderate, or severe. Data analysis in this study used the Shapiro-Wilk test and the Wilcoxon Signed Rank Test. This study obtained results the median severity score decreased from 2 (moderate) before the intervention to 1 (mild) after the intervention. Wilcoxon Signed Rank Test showed a significant reduction in vaginal discharge after intervention (Z = -5.477; p < 0.001) with a large effect size (r = 0.92). From this study, it was found that Curcuma longa extract and piper piper betel leaf can significantly reduce the severity of vaginal discharge and can be considered as a complementary intervention.